The Effect of Dividend Policy and Capital Structure on Firm Value: A Case Study in Vietnam - Nghia Nguyen (The Indonesian Institute of Science and Technology Research, 2025)
Dividend policy represents the portion of corporate profit that companies pay to investors. Capital structure is a crucial corporate policy that indicates the ratio of debt to total assets. This paper aims to investigate the effect of dividend payout and capital structure on firm value in Vietnam. The study utilizes data from publicly traded companies on the Vietnamese Stock Exchanges. The analysis methods used include pooled OLS, and fixed and random effects models. The results reveal that dividend payout policy has a positive effect on the corporate value of Vietnamese publicly traded companies. The proportion of debt usage also exerts a positive effect on firm value. The findings show that corporate size and firm profitability have a significant and positive relationship with firm value. The study's results are useful for planning corporate dividend and capital structure policies.